Language Stress and Anxiety among the ESL Students: A Case Study of First Year Students in Pakistani Context - Haq, Inam-Ul; Farhat, Perveen Akhter; Iqbal, Sahibzada Wasim (Annals of Human and Social Sciences, 2022)
The purpose of this research study was to explore the causes of anxiety level amongst the Pakistani ESL students. A review of the literature was conducted to examine the variables, which were affecting English language learners. The researchers selected quantitative research method and gathered data from 100 participants. The data was analyzed through statistical software namely SPSS; and presented in numerical form by using figures and tables. The results of the present study showed that the level of anxiety differs amongst different ESL students. They feel anxious if they go unprepared in the class. Some of them have fear of communicating with their classmates. Many of them experience anxiety symptoms. Some students avoid classrooms because they lack confidence of communicating in English in a better way. The stakeholders are recommended to understand basic needs of the students. They are recommended to design the English language learning courses in a manner that could reduce their anxiety among these students.